System Dynamics of Quadruple Helix Collaboration for AI-Integrated University Physical Education: Evolution Mechanisms and Optimization Strategies - Wei, Subin; Chen, Zhizhong (Journal of Educational Research and Policies, 2026)
Based on the quadruple helix theory, this study employs literature review and logical analysis to construct a collaborative innovation framework for university sports involving government, technology companies, sports colleges, and the public. It systematically analyzes the role positioning and functional coupling relationships of the quadruple helix's stakeholders and explores the dynamic evolution mechanism and optimization path of multiple stakeholders supported by artificial intelligence technology. The study reveals multi-dimensional challenges faced in the quadruple helix collaboration process, including differences in technology access, misaligned educational philosophies, imbalanced talent resources, and hierarchical institutional barriers. Furthermore, it proposes four paths—technology integration, concept integration, talent aggregation, and institutional innovation—to promote intelligent, systematic, diversified, and efficient development, providing theoretical and practical references for AI-enabled collaborative innovation in university sports.